Comunidad de práctica de los docentes de inglés en pandemia. Un estudio sobre el desarrollo profesional en un instituto de idiomas de Lima - Alvarez Poma, Wilfredo (2025)
In a language institute in Lima, the community of practice of English teachers constitutes an essential space for collaboration and professional development. It emerges as a response to specific challenges in the educational environment, promoting the exchange of ideas and collective improvement. Participants describe the community as a space for dialogue and mutual support, with a particular emphasis on the use of educational technology during the pandemic. Its main goal is to enhance teaching practices through the exchange of practical and useful ideas. This case study, based on interviews and observations, highlights its capacity for teachers’ professional development and its adaptation to challenging circumstances. The community fosters critical thinking and the collaborative distribution of leadership, emphasizing the importance of the leader’s social experience. In summary, this community emerges as a valuable space that positively impacts teaching practice, promoting collaboration and adaptability.